2017
DOI: 10.1016/j.gexplo.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Geogenic cadmium pollution and potential health risks, with emphasis on black shale

Abstract: Cadmium (Cd) is a non-essential trace element that is toxic to humans. Previous studies of Cd in the environment have primarily focused on pollution resulted from anthropogenic sources, but little is known on naturally occurring sources of Cd. This paper aims to review the geochemical distribution of geogenic Cd and associated environmental risk. The source, accumulation, mobility, transportation, and health risk of Cd are discussed in a geo-environmental perspective, with an emphasis on black shale soils. Cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Therefore, zinc and copper pollution were caused not only by traffic and industrial origin, but also by pesticide, fertilizer, and sewage irrigation widely used in greening and daily life waste. Many researchers revealed that fertilizer with high content of Cu and Zn was a source of long-term soil contamination [47][48][49]. Spatial distribution characteristics of metals in the study area suggested that seven elements in urban forest soils of Nanjing were anthropogenic sources: industrial origin, traffic origin, fertilizer and pesticides, which were in total agreement with the PAC and CA results.…”
Section: Spatial Distribution Of Ptes and Peri In The Study Areasupporting
confidence: 76%
“…Therefore, zinc and copper pollution were caused not only by traffic and industrial origin, but also by pesticide, fertilizer, and sewage irrigation widely used in greening and daily life waste. Many researchers revealed that fertilizer with high content of Cu and Zn was a source of long-term soil contamination [47][48][49]. Spatial distribution characteristics of metals in the study area suggested that seven elements in urban forest soils of Nanjing were anthropogenic sources: industrial origin, traffic origin, fertilizer and pesticides, which were in total agreement with the PAC and CA results.…”
Section: Spatial Distribution Of Ptes and Peri In The Study Areasupporting
confidence: 76%
“…Cadmium is a poisonous and cancer-causing metal that can happen as a food contaminant and worldwide pollutant. Long-term occupational exposure to high cadmium concentrations may cause lung cancer, kidney and bone damages and hematuria [34]. Variance exists on the maximum advisable concentration limit of several metal ions in water.…”
Section: Removal Of Metal Ions With Imprinted Materialsmentioning
confidence: 99%
“…The major natural carrier of Cd are sulphides: sphalerite and pyrite (Schwartz, 2000) with sphalerite showing a rather limited range of Cd concentrations from 0.2 to 1 wt % (Cook et al., 2009). Direct weathering of Cd-bearing ore releases Cd to the environment (Liu et al, 2017), where, depending on the conditions, it can precipitate as Cd-bearing carbonates and sulphosalts (Cabala and Teper, 2007) as well as Cd sulphide -greenockite (e.g. Mogessie et al, 2009).…”
Section: Implications From CD Distribution In Cd-rich Slag On Cd Mobimentioning
confidence: 99%